How student-led organizations shape STEM pre-service teachers’ sense of belonging - Emenaha Miles, Uchenna; Leishsing, Samantha; Solis Rodriguez, Janet (American Journal of STEM Education, 2025)
Student organizations have been shown to have positive effects on students’ wellbeing and academic achievement. This study examines how student-led organizations within a STEM teacher preparation program shape students’ sense of belonging among 27 undergraduate STEM pre-service teachers following the COVID-19 pandemic. Our analysis revealed that participation in student-led organizations was associated with increases in students’ sense of belonging, socioemotional wellbeing, academic outcomes, and connection to the teaching profession. These findings suggest that student-led organizations can play a pivotal role in fostering prospective teachers’ sense of belonging by creating supportive communities that cultivate their professional growth as they prepare to enter the STEM teaching workforce.